Effects of hypothermia on cardiac function in neonates with asphyxia - Zhou, Wen-hao (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2003)
OBJECTIVE: To study the effects of hypothermia on cardiac function in neonates after birth asphyxia